2010
DOI: 10.1371/journal.pone.0008219
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Genomic Characterization of the Genus Vitis

Abstract: Next-generation sequencing technologies promise to dramatically accelerate the use of genetic information for crop improvement by facilitating the genetic mapping of agriculturally important phenotypes. The first step in optimizing the design of genetic mapping studies involves large-scale polymorphism discovery and a subsequent genome-wide assessment of the population structure and pattern of linkage disequilibrium (LD) in the species of interest. In the present study, we provide such an assessment for the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
168
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(175 citation statements)
references
References 33 publications
5
168
0
2
Order By: Relevance
“…Microsatellite and SNP markers have become in the last years the markers of choice for genetic analyses in grapevine, including genetic mapping and QTL identification (Huang et al 2012;Doligez et al 2013;Battilana et al 2013;Barba et al 2014), linkage disequilibrium and association analyses (Emanuelli et al 2010;Barnaud et al 2010;Cardoso et al 2012;Vargas et al 2013), and varietal identification (Myles et al 2010;Cabezas et al 2011;Laucou et al 2011;Migliaro et al 2012). As in many other woody plant species, genetic mapping in grapevine has been carried out using mainly the double pseudo test-cross strategy (Grattapaglia et al 1995), which is based on the study of allelic segregation of markers found in heterozygosis in one or both progenitors of an F 1 progeny.…”
Section: Applications Of the Developed Multiplex Pcrsmentioning
confidence: 99%
“…Microsatellite and SNP markers have become in the last years the markers of choice for genetic analyses in grapevine, including genetic mapping and QTL identification (Huang et al 2012;Doligez et al 2013;Battilana et al 2013;Barba et al 2014), linkage disequilibrium and association analyses (Emanuelli et al 2010;Barnaud et al 2010;Cardoso et al 2012;Vargas et al 2013), and varietal identification (Myles et al 2010;Cabezas et al 2011;Laucou et al 2011;Migliaro et al 2012). As in many other woody plant species, genetic mapping in grapevine has been carried out using mainly the double pseudo test-cross strategy (Grattapaglia et al 1995), which is based on the study of allelic segregation of markers found in heterozygosis in one or both progenitors of an F 1 progeny.…”
Section: Applications Of the Developed Multiplex Pcrsmentioning
confidence: 99%
“…If this situation is common throughout the genome, as suggested by studies in grapevine (Myles et al, 2010), then whole-genome scan association studies in essentially undomesticated populations will require a very large number of SNPs. It is unlikely that all necessary variants will be represented on an array in the near future.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…From these surveys of LD, Kim et al (2007) estimated that B140 000 single-nucleotide polymorphisms (SNPs) would be required for the whole scan of the 125-Mb genome of Arabidopsis, whereas Yan et al (2009) estimated this number between 240 000 and 480 000 SNPs for the 2400-Mb genome of maize. A genome-wide analysis showed that LD is so low in grapevine (r 2 o0.20 even between very close sites in Vitis vinifera) that whole-genome sequencing will be required for genome-wide association analyses (Myles et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This susceptibility to disease, however, is not attributable to a lack of genetic diversity. Vinifera harbors levels of genetic variation an order of magnitude greater than humans and is comparable in diversity to maize (2,3), with polymorphism that dates back tens of millions of years (4). Thus, an environmentally sustainable grape-growing industry will rely on accessing and using the grape's tremendous genetic diversity to develop improved disease-resistant grape cultivars through marker-assisted breeding (5).…”
mentioning
confidence: 99%
“…To this end, we recently discovered over 70,000 high-quality SNPs in the grape using next-generation DNA sequencing (4). From this SNP set, we developed and validated a 9,000-SNP genotyping array (the Vitis9kSNP array).…”
mentioning
confidence: 99%